Exploring how young women with visual impairments navigate their participation in recreational sport - De Vos, Dellicia (Department of Health and Rehabilitation Sciences, 2022)
Regular physical activity is important to improve overall quality of life (WHO, 2011). Improving the physical activity levels of persons with disabilities, however, has not received enough attention. Current global research has focused on identifying barriers that prevent persons with disabilities from participating in recreational sport, but few of these studies were conducted in Africa and even fewer focused on the experiences of women with vision impairments specifically. Further, none of them foregrounded a focus on how participation in recreational sports might be facilitated. This study therefore aimed to explore how women with vision impairments navigate their participation in recreational sports. Narrative inquiry was employed as the study design. Three young women with vision impairments from different communities in the Western Cape, South Africa, were purposely selected. Data was generated in the form of topical life stories and subjected to a rigorous, multi-layered analytic process. This involved ‘narrative analysis' and ‘analysis of narratives' to generate a single overarching theme: “Sport and life as interconnecting circles”. This theme revealed a reciprocal influence between sport and life. Here, ‘life' refers to participation across the broad spectrum of everyday life. The findings revealed that the socialisation of women with vision impairments in their early childhood influenced their ability to navigate their participation in recreational sports. The presence of people as social champions in these women's lives contributed to facilitating the participants' participation in sports and highlighted the importance of the social inclusion of women with vision impairments. The findings call for an embedded way of thinking about the social inclusion of women with vision impairments which allows for an organic evolution of participation in recreational sports. The implication is that sports participation for women with vision impairments would occur naturally and spontaneously if they were included in other spheres of life.